VALIDITY AND RELIABILITY OF THE INDONESIAN VERSION OF THE INTERNATIONAL PHYSICAL ACTIVITY QUESTIONNAIRE AMONG STUDENTS: A CONFIRMATORY ANALYSIS USING THE ACTIGRAPH GT3X+ ACCELEROMETER - Akbar, Muhammad Syagil; Jajat, Jajat; Sultoni, Kuston; Ruhayati, Yati; Suherman, Adang; Nuryanti, Widy Dewi (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Questionnaires and accelerometers are the most commonly used instruments by researchers to analyze physical activity. This study aims to evaluate the relationship between physical activity measurements using two methods: the International Physical Activity Questionnaire (IPAQ) and the Actigraph GT3X+ device. The study sample consisted of 27 male and 23 female students from Universitas Pendidikan Indonesia. The instruments utilized in the research were the Actigraph GT3X+ accelerometer and the IPAQ. Data analysis was conducted by correlating the data obtained from the IPAQ and the Actigraph GT3X+. The results indicated that there was no correlation between IPAQ and Actigraph GT3X+ across various physical activity intensities. Further analysis is required, considering an increased sample size and minimizing self-reporting biases through a more structured approach to achieve more accurate results.